PROFESSIONAL SUCCESS OF FUTURE PSYCHOLOGISTS IN THE RISK SOCIETY - Chugueva, Inna; Kuznetsova, Svitlana (PSYCHOLOGICAL JOURNAL, 2017)
There is considered the problem of professional success of future psychologists in the society of risk. The main psychological components of professional success are described. There is considered the connection of professional success in the risk society with the ability to solve difficult life situations. The expediency of attracting of future psychologists in solving difficult life situations as a value-semantic basis of the personal educational paradigm is substantiated. It has been determined that professional success as a concept has many components of its content, it includes individual, social, economic, functional and activity components, which reveal the meaning of this concept both in general and in every concrete example. Professional success is a certain result, which is created in the process of assimilation, mastering and realization of a person in his or her professional activity. Considering the problem of professional success of future psychologists, it is noted that the professional and personal aspects which are interrelated and mutually related, constitute the essence of the problems of professional development of the individual. The conception of new goals and means, ideological orientation sand forms of organization of educational activity is offered to be taken in to account of requirements of formation and development of the ability to handle both problem situations in general and with situations of risk in particular. It is emphasized that in the society of risk the professional task of a practicing psychologist acquires a new meaning – the formation of a special culture of social and individual life with the observance of there quirements of anthropological, social, psychological safety. It is shown that the profession of psychologist is becoming more practical-orientated, and psychologists are necessary specialists who are called to help the society and every citizen to find answer stourgent issues of the present, to provide psychological support to those who find themselves in difficult life situations. According to the results of the research, it has been shown that professional skills are not yet understood by students in a holistic way of professional activity. Thus, we can conclude that we should help the future psychologists to reveal the situational aspect of professional activity, to reveal the components of professional success precisely in the area of solving difficult life situations, to form psychological readiness for their solution during their professional training.